Early accessibility testing – an automated kit for Android developers - Garcia, Anderson Canale; de Lara, Silvana Maria Affonso; Duarte, Lianna Mara Castro; de Mattos Fortes, Renata Pontin; Rodrigues, Kamila Rios Da Hora (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2023: Proceedings of the 29th Brazilian Symposium on Multimedia and the Web, 2023)
Accessibility in mobile applications enables people with disabilities to carry out daily tasks like other users. There are many sets of guidelines and tools for accessibility tests. However, developers continue to face barriers to meet accessibility requirements while developing mobile applications, resulting in most popular apps having accessibility violations. Based on the literature, we can highlight the most used interface components and where most accessibility violations occur. We argue that by adopting practices familiar to developers and integrating accessibility testing early in coding, we can empower developers to build more accessible applications. This work presents an automated accessibility testing kit for Android apps based on recommendations from literature to overcome accessibility problems faced by visually impaired people. The Automated Accessibility Testing Kit for Android Apps (AATK) is an Android Library to assist developers in creating accessibility tests that can be run within the JVM in seconds. The main goal is to promote more developers’ involvement in integrating accessibility into mobile applications from the coding stage. The kit initially contains five tests for recurring accessibility issues that impact how visually impaired users utilize native apps. The initial usability evaluations of AATK were carried out with undergraduate students enrolled in Software Testing courses. The results indicate greater acceptance among students in the final semesters.